The prevalence of caries, def-t, and DMF-T index of children with Down Syndrome aged 6-14 years old - Azhar, Nor Fatihah; Riyanti, Eriska; Musnamirwan, Iwan Ahmad (Universitas Padjadjaran, 2012)
Down syndrome is a common genetic disorder also known as Trisomy 21. There are special orofacial features of children with Down syndrome in contrast to normal children. The increasing occurrence of dental caries in Down syndrome children may be caused by the exposure towards cariogenic foods nowadays. This research was aimed to determine the prevalence of caries, def-t, and DMF-T index of 6-14 years old children with Down syndrome at Bandung in 2011. This study was a descriptive study with the surveying technique. The population of this research was the Down syndrome students of Special School (SLB) in Bandung City region with the age range of 6-14 years old. The Special Schools participated in this study were Muhammadiyah Special School; YPLB C-Special School; Asih Manunggal C- Special School; Terate S-Special School; Aditya Grahita BC-Special School; and YPLB Cipaganti BC-Special School. The sample of this research was 30 students. The caries prevalence, def-t, and DMF-T index of the students was measured by the examination of decayed, extracted or missing, and filled teeth. The research results showed that the prevalence of caries was 93%, while the def-t index was 3.03 and DMF-T index was 6.1. The conclusion of this research was the caries prevalence of children with Down syndrome was very high, whereas the def-t index was categorized in the moderate level, and the DMF-T index was categorized in the high level.